PENGARUH FIRM SIZE, SALES GROWTH, DAN ROA TERHADAP PENGHINDARAN PAJAK DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Jemima Christy; Subagyo Subagyo (Universitas Kristen Krida Wacana, 2019)
This study aimed to examine the effect of firm size, sales growth, return of asset, the interaction between the audit committee and firm size, the interaction between the audit committee and sales growth as well as the interaction between the audit committee and return of asset on tax avoidance by moderation by the audit committee. The research data uses secondary data (financial statements) with a purposive sampling method. The regression model used in this study is a multiple linear regression model with E-views 9. Research Samples were 258 data of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The results of this study indicate that sales growth and return of assets has no significant effect on tax avoidance, and firm size has a significant effect on tax avoidance. The audit committee cannot moderate the relationship of return of assets and sales growth on tax avoidance, but can moderate the relationship between firm size and tax avoidance.Keywords: firm size, sales growth, return of asset, audit committee, tax avoidance